2022
DOI: 10.3390/cancers14235734
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cancer Antigen 125 Level as Predictor for Complete Cytoreduction in Ovarian Cancer: A Prospective Cohort Study and Systematic Review

Abstract: Background: The tumor marker ‘cancer antigen 125’ (CA-125) plays a role in the management of women with advanced stage ovarian cancer. This study aims to describe the predictive value of pre-treatment CA-125 level and the reduction after neoadjuvant chemotherapy (NACT) on surgical outcome. Methods: A systematic review and a prospective clinical study were performed. Multiple databases were searched from database inception to April 2022. The clinical study is part of a randomized controlled trial named “PlaComO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
0
1
Order By: Relevance
“…Although previous studies demonstrated a correlation between the percentage of decrease in CA-125 after NACT and surgical outcome, we neither found an association between the preoperative value of CA-125 nor the reduction rate of CA-125 level after NACT and unresectable disease. One study reported a significant relation between CA-125 level and complete CRS in multivariable analysis, while all other studies did not perform a multivariable analysis [15][16][17]. Although the study by Gupta et al found a significant correlation between a >95% decrease in preoperative CA-125 level and complete CRS, our study showed that this does not guarantee complete CRS.…”
Section: Ca-125contrasting
confidence: 77%
“…Although previous studies demonstrated a correlation between the percentage of decrease in CA-125 after NACT and surgical outcome, we neither found an association between the preoperative value of CA-125 nor the reduction rate of CA-125 level after NACT and unresectable disease. One study reported a significant relation between CA-125 level and complete CRS in multivariable analysis, while all other studies did not perform a multivariable analysis [15][16][17]. Although the study by Gupta et al found a significant correlation between a >95% decrease in preoperative CA-125 level and complete CRS, our study showed that this does not guarantee complete CRS.…”
Section: Ca-125contrasting
confidence: 77%
“…This work coincides with the interval cytoreduction percentages according to our case series. 22 However, only the absence of ascites and peritoneal carcinomatosis during surgery, FIGO stage IIIB/IIIC and high-grade serous histology were significant independent predictors of CC in interval surgery, demonstrated in multivariate analysis. This analysis coincides with our review of cases where 100% of the histology was high-grade serous, which could explain the high response rate to NACT and CC.…”
Section: Discussionmentioning
confidence: 87%
“…6,12,13,[15][16][17][18][19][20][21] Results from a systematic review by Brons et al indicated a significant relationship between lower preoperative CA-125 values and CC in patients who underwent interval surgery. 22 However, the definitions of normal CA-125 value and optimal CA-125 reduction cut-off values varied between studies, denoting that the effect of CA-125 reduction rate after NACT could not be directly compared in the surgical outcome. The studies included in that systematic review did not report the effect of ascites or peritoneal carcinomatosis and lacked multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%